Toward justice and social transformation? Appealing to the tradition against the tradition - Naude, Piet J. (HTS teologiese studies, 2017)
This article starts with a brief statement on the well-known contradictory nature of the Reformed tradition in South Africa, defending injustice and struggling for justice in the name of the same tradition. By following the work of Reformed systematic theologian D.J. Smit, it argues that the justice-affirming potential of the Reformed tradition is a hermeneutical task built on three specific re-interpretations: (1) the reinterpretation of Scripture from the perspective of the weak, the poor and the oppressed (against a hermeneutic of creation orders and God-willed division of people) (2) a rereading of John Calvin to affirm the dignity and freedom of all humans (against the grain of neo-Calvinist interpretations) (3) a rereading of Karl Barth with a focus on God’s inclusive grace, Christian confessions and the nature of the Christian life (against the limitation of his influence because of his perceived actualistic view on Scripture or unscientific, foundational methodology). The article closes with a brief look into the agenda for social transformation faced by us in the second decade of the 21st century, and under what conditions the Reformed faith will be able to make an enduring contribution to public life in (South) Africa.